Effectiveness of Non-Communicable Disease Control Policies: Comparative Study of Cervical Cancer Treatment Indonesia and Australia 2017-2021 - Purba, Pricilla Philia Br.; Fahadayna, Adhi C. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study explores the relationship between Universal Health Coverage (UHC) and the incidence of cervical cancer through a comparative analysis between Indonesia and Australia. The primary objective is to understand how healthcare coverage influences the reporting of cervical cancer cases in two countries with differing health system structures. The analysis indicates that higher UHC coverage tends to be associated with increased detection of cervical cancer cases, highlighting the critical role of screening systems and access to healthcare services. Furthermore, there are significant differences in healthcare structure and quality between the two countries, which impact the overall disease burden. This research underscores the importance of strengthening screening and vaccination programs, particularly in countries with limited UHC coverage. The findings are expected to contribute to the advancement of future research and serve as a foundation for the development of more inclusive and sustainable health policies.